ASSOCIATION OF TRICUSPID REGURGITATION AND SEVERITY OF MITRAL STENOSIS IN PATIENTS WITH RHEUMATIC HEART DISEASE - Ahmed, Rehan; Kazmi, Nasir; Naz, Farhat; Malik, Saqib; Gillani, Saima (Journal of Ayub Medical College Abbottabad, 2016)
Background: Rheumatic heart disease is a common ailment in Pakistan and Mitral stenosis is its flag bearer Severity of mitral stenosis is the key factor in deciding for mitral valve surgery. Methods: This case series study was conducted at Ayub Teaching Hospital .Cases of Rheumatic heart disease with mitral stenosis were diagnosed clinically. 2D echocardiography was used to find severity of mitral stenosis. Data was entered into SPSS-17.0 and results were recorded and analysed. Pearson's two tailed correlation was used to find the correlation between presence of tricuspid regurgitation in patients with severe mitral stenosis, p was <0.05. Results: A total 35 patients with pure mitral stenosis were included in study, out of which 8 were male and 27 were females. Mean age in males was 34.5±15.85 years while in females it was 31±8 years. Twenty-two out of 35 (62.86%) patients had tricuspid regurgitation while 13 out 35 (37.14%) had no tricuspid regurgitation. Mean (MVA) mitral valve area in patients with tricuspid regurgitation was 0.84±0.3 cm2 while mean (MVA) mitral valve area in patients without tricuspid regurgitation was 1.83±0.7 cm2. Mean left atrial (L.A) size was 45.23±1.5mm2 in patients with tricuspid regurgitation, while it was 44.13±6.14mm2 in patients without tricuspid regurgitation. Mean RSVP was 57.5mmHg in patients with tricuspid regurgitation while RSVP could not be calculated in patients without tricuspid regurgitation. Conclusions: It was concluded that tricuspid regurgitation was strongly associated with severe mitral stenosis as almost all patients with severe mitral stenosis had tricuspid regurgitation and none of the patients with mild mitral stenosis had tricuspid regurgitation. Keywords: Rheumatic heart disease, Mitral Stenosis, Tricuspid regurgitation, Mitral Valve Area, Right Ventricular Systolic Pressure.